THE TEACHINGS OF CATUR MARGA: Critical Reflection on Constructivism Learning and its Relevance to UNESCO's Four Pillars of Education - I Ketut Wisarja; Ni Nyoman Suastini; Ni Wayan Aryani (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2024)
The general assumption that education is a means of acquiring knowledge is indisputable, but the opinion that education is only obtained in a formalist environment is very naive, because it excludes other possibilities where education is also obtained from non-formal education models (andragogical), such as; pasraman education, ashram education, pesantren education, etc. The conservative paradigm with all its attributes, such as; educational fundalism, educational intellectualism, and educational conservatism, is basically more towards achieving a quo-vadis form of education and maintaining harmonization. The conservative paradigm with all its attributes, such as; educational fundalism, educational intellectualism, and educational conservatism, is basically more towards achieving a quo-vadis form of education and maintaining harmony only, without any criticism of all pre-conditions and post-conditions of existing knowledge and awareness. This concept is basically not too far from a mere "stabilizing" view of imprisoning educational practices (shackling education), which in turn raises the assumption/stigma that even educational intellectualism is inseparable from the subject of interests. This article aims to review and analyze the teachings of Catur Marga as a pasraman education pattern that adopts gradual and tiered educational patterns which in today's educational terms are called constructivism learning patterns. This pattern is widely applied with the aim that individuals and communities of learners are able to construct their own knowledge through a series of learning experiences, which turns out that this pattern is in line with the four pillars of education initiated by UNESCO, which gradually include; (1) learning to know, (2) learning to do, (3) learning to live together, and (4) learning to be. Keywords: Catur Marga, educational constructivism, four pillars of education, and critical reflection of the educational paradigm in Indonesia.